SISTEM INFORMASI AKUNTANSI MANAJEMEN, SISTEM INFORMASI AKUNTANSI, DAN KINERJA MANAJERIAL - Yana Rochdiana Hadiyat (JRAK, 2020)
This study aims to determine empirical evidence of the influence of the characteristics of management accounting information systems on managerial performance moderated of accounting information systems. This study found that digital skills and aggregation have a higher influence on managerial performance than the effect of boardscope, timelines, aggregation, and integration. The population in this study were leaders and staff of state-owned enterprises that were limited liability companies in West Java. The number of samples used was seventytwo. The expected benefit is to provide input to the company as a material for consideration in designing a company’s management accounting system tailored to business strategy, which has an impact on improving managerial performance.